Discounted Life : The Price of Global Surrogacy in India - Rudrappa, Sharmila, 1966- (Book collections on Project MUSE., 2016)
Drawing from rich interviews with surrogate mothers and egg donors in Bangalore, as well as 20 straight and gay couples in the US and Australia, this work focuses on the processes of social and market exchange in transnational surrogacy. Sharmila Rudrappa interrogates the creation and maintenance of reproductive labour markets, the function of agencies and surrogacy brokers, and how women become surrogate mothers. She argues that the reproductive industry is organised to control and disempower women workers and yet her interviews reveal that, by and large, the surrogate mothers in Bangalore found the experience life affirming. Rudrappa explores this tension, and the lived realities of many surrogate mothers whose deepening bodily commodification is paradoxically experienced as a revitalising life development.